Cryostorage and retransplantation of ovarian tissue as an infertility treatment - Amorim, Christiani A. (2019)
While still considered an experimental procedure in most countries, ovarian tissue cryopreservation and transplantation has been increasingly applied worldwide to restore fertility in patients with malignant and non-malignant pathologies with risk of premature ovarian insufficiency. It has yielded more than 130 live births up to now and almost all transplanted patients recovered their ovarian function. This study summarizes ovarian tissue cryopreservation and transplantation indications, procedures, their efficacy and main results and proposes different strategies to improve this strategy. Although the main focus of this study is on ovarian tissue cryopreservation and transplantation as a strategy to restore fertility, we believe that it is also important to discuss other applications for this approach. (C) 2018 Elsevier Ltd. All rights reserved.